口腔内指標を判定するための検査方法 (2021)
口腔内指標を判定し得る口腔内指標を判定するための検査方法を提供することを課題とし、測定プローブを用いて、被験者の付着歯肉内部の超音波画像を取得する画像取得工程と、超音波画像の平均輝度を取得する平均輝度取得工程と、平均輝度と口腔内指標の基準を参照して、被験者の口腔内指標を判定する指標判定工程と、を有する口腔内指標を判定するための検査方法。【選択図】なし Provided is a testing method for determining an oral indicator by which an oral indicator can be determined. The testing method for determining an oral indicator includes an image acquisition step of acquiring an ultrasonic image of an inside of an attached gingiva of a subject, using a measurement probe, an average brightness acquisition step of acquiring average brightness of the ultrasonic image, and an indicator determination step of determining an oral indicator of the subject by referring to the average brightness and a reference of an oral indicator.